2021
DOI: 10.1002/fsn3.2518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of turmeric on reducing heterocyclic aromatic amines in Chinese tradition braised meat products and the underlying mechanism

Abstract: Heterocyclic aromatic amines (HAAs) are carcinogenic and mutagenic substances produced during the high-temperature processing of higsh protein meat and commonly found in hightemperature meat products such as frying and barbecue (Adamson et al., 2010;Jinap et al., 2015). Until now, more than 25 kinds of HAAs have been identified, and they could be divided into two categories according to the formation process: Aminoimidazo azaarenes and Amino-carboline congeners (Cheng et al., 2010;Oz & Cakmak, 2016). In previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…These were in agreement with previous research using other antioxidant. Curcumin has been reported to decrease the contents of β-CHAs by inhibiting the production of carbonyl compounds ( Wang et al, 2021 ). It has been widely accepted that antioxidants have excellent ability to remove free radicals ( Meurillon and Engel, 2016 ), which may contribute to the inhibitory effects on the formation of carbonyl compounds.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These were in agreement with previous research using other antioxidant. Curcumin has been reported to decrease the contents of β-CHAs by inhibiting the production of carbonyl compounds ( Wang et al, 2021 ). It has been widely accepted that antioxidants have excellent ability to remove free radicals ( Meurillon and Engel, 2016 ), which may contribute to the inhibitory effects on the formation of carbonyl compounds.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the free radicals generated in the lipid oxidation process are also the potential initiators of protein carbonylation ( Estevez, 2011 ), which may lead to the β-CHAs production ( Khan et al, 2022 ). Many studies have shown that the addition of antioxidant compounds to meat products was an effective way to scavenge the free radicals produced ( Selani et al, 2011 ; Tengilimoglu-Metin et al, 2017 ; Wang et al, 2021 ), thus alleviated the lipid and protein oxidation. The OWSF treatment also had the ability to keep the free radical content in the oil at a low level by avoiding repeated heating of food residues ( Ma et al, 2016 ), thus decreased the products of lipid and protein oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food-derived antioxidants, which are naturally abundant in phenolic compounds, have the ability to inhibit the formation of HAAs by scavenging free radicals in the reaction system ( Hidalgo, Navarro, and Zamora 2018 ). Examples of such antioxidants include dried apple peels, green tea, olive oil, beer/red wine, rosemary, garlic, onion, red chili, paprika, ginger, turmeric, and black pepper, which have been shown to inhibit the formation of HAAs by scavenging pyrazine cation radicals or carbon-centered radicals in both chemical models and cooked meat ( Wang et al, 2021 , Zeng et al, 2018 , Bao et al, 2020 ). Previous studies have suggested that the stronger the free radical scavenging activity is, the greater the inhibition of HAAs.…”
Section: Inhibition Mechanism Of Haasmentioning
confidence: 99%
“…Herbs and spices due to the content of various bioactive compounds i.a., polyphenols also exhibit an inhibitory effect against HAAs formation. For instance, turmeric at 5% concentration decreased harman content by about 94.8% while norharman by about 49.56% [ 69 ]. Similar effects were documented for red pepper [ 70 ], Sichuan pepper, black cumin [ 86 ], rosemary, turmeric, galangal, fingerroot [ 87 ], thyme, savory, and oregano [ 88 ].…”
Section: Parameters Affecting Haas Content In Cooked Meatmentioning
confidence: 99%